Construcción de prácticas de laboratorio bajo la iniciativa CDIO a partir de la implementación de las técnicas de control PID y LQR en un minidrone parrot rolling spider para la universidad Antonio Nariño. (2020)
In this work, two laboratory guides are developed focused on control strategies such as the Proportional Integral Derivative (PID) and the Quadratic Linear Regulator (known in its acronym in English as LQR), so that the student of the Antonio Nariño University together with the designated teacher for the control and control theory II courses; Master the concepts associated with the aforementioned controllers by applying them to the height variable of a Drone specifically in the MiniDrone Parrot Rolling Spider, with the different techniques involved in these controls. Additionally, the two aforementioned control systems are developed and presented in a simulated way, to provide solutions to each laboratory practice independently, so that the student has tools to consolidate knowledge in the area and that may be useful for your work. Said simulations were carried out in Matlab software, specifically in the Simulink program, since there are different Toolboxes such as the Simulink Support Package for Parrot Minidrones, which, employing block programming, facilitates their understanding and realization. It should be noted that laboratory practices are established under a learning modality based on the CDIO methodology, so that they constitute a design and implementation experience.